Neuroendocrine alterations impair enamel mineralization, tooth eruption and saliva in rats. - Sassaki, Kikue Takebayashi; Delbem, Alberto Carlos Botazzo [UNESP]; dos Santos, Otoniel Antonio; Shimabucoro, Carlos Eduardo; Nakamune, Ana Cláudia de Melo Stevanato [UNESP]; Bedran-de-Castro, João César; Oliveira-Filho, Ricardo Martins (FapUNIFESP (SciELO), 2003)
Neonatal administration of monosodium glutamate (MSG) in rats causes definite neuroendocrine disturbances which lead to alterations in many organ systems. The possibility that MSG could affect tooth and salivary gland physiology was examined in this paper. Male and female pups were injected subcutaneously with MSG (4 mg/g BW) once a day at the 2nd, 4th, 6th, 8th and 10th day after birth. Control animals were injected with saline, following the same schedule. Lower incisor eruption was determined between the 4th and the 10th postnatal days, and the eruption rate was measured between the 43rd and the 67th days of age. Pilocarpine-stimulated salivary flow was measured at 3 months of age; protein and amylase contents were thereby determined. The animals treated with MSG showed significant reductions in the salivary flow (males, -27%; females, -40%) and in the weight of submandibular glands (about -12%). Body weight reduction was only about 7% for males, and did not vary in females. Saliva of MSG-treated rats had increased concentrations of total proteins and amylase activity. The eruption of lower incisors occurred earlier in MSG-treated rats than in the control group, but on the other hand the eruption rate was significantly slowed down. The incisor microhardness was found to be lower than that of control rats. Our results show that neonatal MSG treatment causes well-defined oral disturbances in adulthood in rats, including salivary flow reduction, which coexisted with unaltered protein synthesis, and disturbances of dental mineralization and eruption. These data support the view that some MSG-sensitive hypothalamic nuclei have an important modulatory effect on the factors which determine caries susceptibility.
Keywords: amylase; food additive; glutamate sodium; animal; body weight; drug effect; enamel; female; male; metabolism; neurosecretion; newborn; rat; saliva; salivary gland; salivation; sex difference; tooth eruption; Wistar rat; Amylases; Animals; Animals, Newborn; Body Weight; Dental Enamel; Female; Food Additives; Male; Neurosecretory Systems; Rats; Rats, Wistar; Saliva; Salivary Glands; Salivation; Sex Factors; Sodium Glutamate; Tooth Eruption